Clinical stem cell therapy in oral and craniofacial bone regeneration: a systematic review and meta-analysis - Hazrati, Parham; Alanazi, Abdulmohsen; Alrmali, Abdusalam E.; Galindo-Fernandez, Pablo; Kassem, Hazar; Kaigler, Darnell (Frontiers in Bioengineering and Biotechnology, 2026)
Craniomaxillofacial bone regeneration poses significant clinical challenges due to the anatomical complexity of this region and the inherent limitations of conventional reconstructive techniques. Stem cell-based therapies have emerged as a promising alternative in that stem cells harness the capacities of multilineage differentiation and paracrine signaling to enhance tissue regeneration. Nonetheless, the overall clinical efficacy of stem cell therapy remains a subject of debate. In this systematic review and meta-analysis, we aimed to comprehensively evaluate the safety and effectiveness of stem cell therapy in oral and craniofacial bone regeneration. A comprehensive search of PubMed/MEDLINE, Scopus, Embase, and Web of Science was conducted in July 2024, identifying 59 eligible prospective studies—including randomized controlled trials (RCTs), controlled clinical trials and single-arm studies—involving more than five participants each. Risk of bias was assessed using the Cochrane RoB 2 tool for randomized studies and ROBINS-I for non-randomized studies. The included studies encompassed a broad range of surgical indications, such as alveolar cleft repair, alveolar ridge augmentation, sinus floor augmentation, periodontal defect regeneration, mandibular fracture management, pathological bone defect repair, and temporomandibular joint disorders. Over three-quarters of studies utilized bone marrow aspirate (BMA) and/or mesenchymal stem cells (MSCs), either alone or combined with biomaterial scaffolds. Across diverse procedures, stem cell therapy was associated with clinical and histological benefits, especially in the quality and maturity of regenerated bone. Meta-analysis showed that the addition of stem cells significantly improved the histologic quality of regenerated bone (p = 0.0446), although this enhancement was not evident in radiographic assessments (p = 0.1094). Additionally, meta-analyses demonstrated that stem cell therapy did not result in significant improvements in periodontal clinical attachment level (CAL) gain (p = 0.0730) or linear bone height (p = 0.1858) and width (p = 0.8323) compared to conventional treatments. Notably, volumetric (3D) radiographic assessments indicated significantly enhanced bone volume regeneration in stem cell-treated groups (p = 0.0218). Overall, stem cell therapy shows promising potential in craniomaxillofacial bone regeneration, but heterogeneity among studies underscores the need for further standardized clinical trials to establish definitive benefits, as well as consistent reporting.Systematic review registrationThe protocol of this systematic review was registered on PROSPERO with the ID CRD42024619352.